Ocelová konstrukce mostu na pozemní komunikaci - Vlček, Radek (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Náplní diplomové práce je návrh ocelové nosné konstrukce mostu o rozpětí 31+74+31m s dolní mostovkou převádějící silnici II. třídy v oblasti města Olomouc. Mostovka je tvořená ocelobetonovou deskou spřaženou s příčníky. Řešení bylo zaměřeno na použití obloukové konstrukce ve střední části mostu s různým nakloněním oblouků vůči vodorovné středové ose mostu. V rámci řešení byly vypočítány čtyři varianty. Nejvýhodnější z nich byla vybrána a detailněji zpracována. Výpočty jsou zpracovány podle platných normativů ČSN EN.

The content of the thesis is a proposal of steel load-bearing structure (carrying structure of a steel) bridge of the span of 31+74+31m with the bottom bridge deck taking over the second-class road in the territory of Olomouc city. The bridge deck is created by composite steel-concrete slab with crossbars. The solution was focused on using arched construction in the middle of the bridge with different tilt of arches to the horizontal central axis of the bridge. Under the term of the solution four alternatives have been calculated. The most optimal solution was selected and processed in detail. The calculations were made in compliance with the Czech technical norms ČSN EN.
Steel structure of the bridge on the road
Keywords: nosná konstrukce; ocel; obloukový most; silniční most; nakloněný oblouk; spřažená ocelobetonová deska; dolní mostovka; silnice II. třídy; load-bearing structure; steel; arched bridge; road bridge; inclined arch; composite steel-concrete slab; bottom bridge deck; second-class road